2012
DOI: 10.1080/01431161.2012.716540
|View full text |Cite
|
Sign up to set email alerts
|

Land surface emissivity retrieval from satellite data

Abstract: As an intrinsic property of natural materials, land surface emissivity (LSE) is an important surface parameter and can be derived from the emitted radiance measured from space. Besides radiometric calibration and cloud detection, two main problems need to be resolved to obtain LSE values from space measurements. These problems are often referred to as land surface temperature (LST) and emissivity separation from radiance at ground level and as atmospheric corrections in the literature. To date, many LSE retrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
217
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 409 publications
(219 citation statements)
references
References 121 publications
1
217
0
1
Order By: Relevance
“…For the ground surface, the components composing the surface are the main factors determining the ground emissivity [33][34][35]. Many effective methods have been approved to estimate the emissivity for LST retrieval [36,37].…”
Section: Determination Of Ground Emissivitymentioning
confidence: 99%
“…For the ground surface, the components composing the surface are the main factors determining the ground emissivity [33][34][35]. Many effective methods have been approved to estimate the emissivity for LST retrieval [36,37].…”
Section: Determination Of Ground Emissivitymentioning
confidence: 99%
“…Previous studies indicated that the ground emissivity has a property of variation with the viewing angles [41][42][43][44][45][46]. However, variations in the ground emissivity with the viewing angle is usually very small when the View Zenith Angle (VZA) is smaller than 60 • , especially when the angle is smaller than 40 • [41,44].…”
Section: Emissivity Determinationmentioning
confidence: 97%
“…The four ground surfaces examined in our study are very typical: water, concrete, bare soil, and grass. The emissivities of these typical surfaces have been examined in many studies [38,[40][41][42][43][44][45][46] because they are central in shaping the environmental quality of the earth's surface.…”
Section: Emissivity Determinationmentioning
confidence: 99%
“…As it is known, LST estimation requires emissivity correction [39][40][41][42]. Therefore, during this process we calculate the average emissivity for 4 th and 5 th AVHRR channel, denoted as ϵ AVHRR and the difference of these channels' emissivity ∆ϵ AVHRR .…”
Section: Lst Estimationmentioning
confidence: 99%